Aplication of the Criminal Law in time as for Thefts (art. 228- 229) - Moise, Andrei Emil (Technium Social Sciences Journal, 2023)
The penal law contains an ensemble of norms; rules of conduit which are enforced by criminal penalties. The penal law in reagard of theft is mandatory from the moment of its enforcement and it lasts, in time, until its abrogation. During the time of the enforcement, the penal law is active and is applied to all committed offences. Time limitation of the penal law represents an important part of the theory of penal law, first, because the penal law enforcement is limited in time, and second, the offences are committed in relation with the penal law. So, the penal law is applied to all crimes against patrimony offences committed while the penal law is enforced (active).The penal law doesn’t apply to the offences committed prior to its enforcement (the law is not retroactive), or to those committed after the law was abrogated (ultraactivity).The study also refers to the situation of concurrence of the offencesinregard to theft crimes, the duration and limits of the efficiency of the penal law, retroactivity, and abolition of an offence, applying the mitior lex principle, the cases when the penal law is retroactive or ultraactive.